2018
DOI: 10.31661/jbpe.v0i0.967
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation the FLAIR Sensitivity and DWI Post-inject in Comparison with Delayed Enhancement T1w for Better Detection of Active MS Lesions

Abstract: Background: Multiple sclerosis (MS) is a chronic, typically progressive and most common autoimmune disease which damaged the central nervous system. According to the reports in 2008, this disorder has affected 2 and 2.5 million people globally. While the reason is not clear, proposed causes for this include immunologic, environmental, infectious and genetic factors, and sexuality. MS can cause many symptoms, including blurred vision, loss of balance, poor coordination, slurred speech, tremors, numbness, extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
0
0
1
Order By: Relevance
“…This was determined by describing active plaques as ultra-bright in comparison with pre-contrast FLAIR images and using subtraction images to confirm the presence of enhancement. Our findings were in line with another study [18] which concluded that CE-FLAIR had the highest sensitivity comparing to CE-T1WI, DWI & ADC in detection of active MS plaques due to the CSF signal suppression in FLAIR, thus offering enough TR time recovery in active enhanced plaques. In their study higher number of active MS plaques in supratentorial region was found on CE-FLAIR comparing to CE-T1WI.…”
Section: Discussionsupporting
confidence: 92%
“…This was determined by describing active plaques as ultra-bright in comparison with pre-contrast FLAIR images and using subtraction images to confirm the presence of enhancement. Our findings were in line with another study [18] which concluded that CE-FLAIR had the highest sensitivity comparing to CE-T1WI, DWI & ADC in detection of active MS plaques due to the CSF signal suppression in FLAIR, thus offering enough TR time recovery in active enhanced plaques. In their study higher number of active MS plaques in supratentorial region was found on CE-FLAIR comparing to CE-T1WI.…”
Section: Discussionsupporting
confidence: 92%
“…МРТ є найбільш чутливим методом виявлення навіть безсимптомної дисемінації уражень. Чутливість цього методу діагностики РС протягом першого року після одноразового нападу становить 94 %, специфічність -83 % [15].…”
Section: вступunclassified